Physico-mechanical properties polypropylene/ethylene-propylene diene monomer (PP/EPDM) binary blends - Josephine Lai, Chang Hui; Ramash, K.; Ratnam, C. T.; Rubiyah, Baini; Nur Amalina Shairah, Abdul Samat (Instituto de Ciencias Aplicadas y Tecnología (ICAT), 2022)
The aim of this study was to develop radiation sterilized polypropylene/ethylene-propylene diene monomer (PP/EPDM) binary blends using melt blending and the mechanical properties of the blends were studied. The PP/EPDM binary blends were prepared in the ratios of 80:20, 60:40, 50:50, 40:60 and 20:80. The binary blends were then compressed for 12 minutes using the hot and cold press machine and were cut into 1mm, 3mm and 6mm thickness for tensile test, impact test, hardness test and Fourier transform infrared spectroscopy analysis. The results showed that higher EPDM content binary blends were more elastic and had better energy absorption compared to lower EPDM ratio binary blends. With the introduction of a 100kGy radiation dose, the binary blends performed better in the Young’s modulus with crosslinking formed within the molecules. Among the PP/EPDM binary blends, 20:80 PP/EPDM blends performed the best in both physical and mechanical properties. This binary blend was suitable for medical devices.